Parallel Crises: The Underlying Science Infodemic Revealed by the COVID-19 Pandemic (International Journal of Mass Communication, 2025)
This study examines the relationship between news consumption behaviors and credibility assessments during the COVID-19 pandemic. The researchers surveyed and interviewed participants and found evidence that political ideology and demographics significantly relate to news-seeking practices, trust in sources, and knowledge about the virus. Participants struggled to articulate coherent fact-checking strategies. The conflation of news and information resulted in widespread distrust. This study underscores the need for comprehensive news literacy education to generate critical thinking toward and informed engagement with news sources in a public health crisis.